From Social Assistance to Disaster Insurance Schemes: The Evolution of Financing Policy Disaster Risk from the Perspective of Narrative Literature Review - Pristiwanto Bani (Cahaya Abadi Publisher, 2026)
Natural disasters are a significant source of fiscal risk for developing countries, including Indonesia, which has a high level of disaster vulnerability. So far, disaster financing in Indonesia remains dominated by a post-disaster social assistance approach that is reactive and depends on the State Revenue and Expenditure Budget (APBN). This approach has limitations: it can increase fiscal pressures and does not provide a long-term risk-management mechanism. This study aims to analyze the evolution of disaster risk financing policies from a social assistance approach to a disaster insurance scheme, and to formulate an integrative model of disaster risk financing relevant to Indonesia. The research uses the Narrative Literature Review (NLR) method by examining academic literature, international policy reports, and regulations related to disaster risk financing for the period 2016–2025. The results of the study show that the evolution of disaster financing policies comprises three main phases: the social assistance approach, the hybrid approach based on risk layering, and the development of disaster insurance schemes, including parametric insurance. The risk-layering approach enables more efficient risk sharing through risk retention, risk transfer, and risk-sharing mechanisms. This study proposes an integrative model of disaster risk financing consisting of government reserve funds, compulsory property insurance in high-risk areas, national and international reinsurance, and the use of capital market instruments such as catastrophe bonds to strengthen fiscal resilience and post-disaster financing stability.